The journey - Lasky, Kathryn (New York : Scholastic, 2003)
Wishing to fight off evil that exists among the owls of the Great Ga'Hoole Tree, Soren, Gylfie, Twilight, and Digger must endure harsh training from the elders to become Ga'Hoolian owls, and carry out their good deeds.
Keywords: Owls -- Juvenile fiction; Gylfie (Fictitious character) -- Juvenile fiction; Soren (Fictitious character) -- Juvenile fiction; Twilight (Fictitious character) -- Juvenile fiction; Digger (Fictitious character) -- Juvenile fiction; Tyto (Imaginary place) -- Juvenile fiction